Aesthetic Normativity and Knowing How to Go On - Ginsborg, Hannah (Con-Textos Kantianos. International Journal of Philosophy, 2020)
This paper addresses a problem about aesthetic normativity raised by Kant. Can aesthetic experiences be appropriate or inappropriate to their objects? And, if so, how is that possible given that, according to Kant, aesthetic experience is not objective? Kant thought the answer to the first question was yes. But his official answer to the second question, in terms of the free play of the faculties, is obscure. The paper offers a clearer answer, inspired by Kant, which invokes Wittgenstein’s notion of “knowing how to go on.” Aesthetic normativity is problematic only on the assumption that claims to the normativity of one’s responses to things must be based on the recognition of objective properties of those things. However, Wittgenstein’s discussion shows that we need not accept that assumption. There can be legitimate claims to the normativity of one’s responses which do not rely on those responses’ reflecting appreciation of objective facts.